Word - Forming Bases and their Variability (on the Material of the Russian language) - Sheremetyeva, Anna; Shchitka, Nelya; Khalilov, Farhad; Rogozinnikova, Nina; Ataeva, Ranusha (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to the study of objects of the lexical and grammatical levels of the Russian language in the light of the general theory of linguistic variability, which provides for the study of variation as one of the fundamental properties of the language system. The aim of the article is a comprehensive description of the word-formation foundations of Russian nouns and adjectives at various levels of word formation. The article analyzes the variational possibilities of word-formation bases on the material of the Russian language. A characteristic is given of the variant foundations of nouns and adjectives in the structure of word forming nest (word - formation nests). The word-forming nest most fully and consistently demonstrates the variational capabilities of stems with different categorical meanings. Reflecting the stepped nature of Russian word formation, the nest as a whole indicates the nature of the relationship between the formative and word-formation bases in chains and paradigms. Particular attention is paid to the general characteristics of the foundations of the Russian word in the inflection and word formation, the secondary character of the word formation foundations and their dependence on the foundations of the formation are shown.